Regulation of iron homeostasis by microRNAs - Castoldi, Mirco; Muckenthaler, Martina (Cellular and molecular life sciences, 2012)
Iron homeostasis is maintained at the cellular and systemic levels to assure adequate iron supply while preventing iron overload. The identification of genes mutated in patients with iron-related disorders or animal models with imbalances of iron homeostasis gave insight into the molecular mechanisms underlying processes critical for balancing iron levels, such as iron uptake, storage, export, and monitoring of available iron. MicroRNAs control genes involved in some of these processes adding an additional level of complexity to the regulation of iron metabolism. This review summarizes recent advances how miRNAs regulate iron homeostasis.
Gesehen am 03.05.2018